SISTEM PENGENDALIAN MUTU MELALUI PENDEKATAN HAZARD ANALYSIS AND CRITICAL CONTROL POINT (HACCP) PADA PENGELOLAAN MAKANAN CATERING - Grace Juni Gressilda Louisa Sine (Kupang Journal of Food and Nutrition Research, 2020)
This study aims to determine the food quality control system at UD.Teti Boga Catering. As for the background of this writing because food safety is still an important issue in the food sector in Indonesia and needs special attention in food control. Food control that relies on the final product test cannot compensate for the rapid progress in the food industry, and cannot guarantee the safety of food circulating in the market. Therefore, food quality assurance called HACCP (Hazard Analysis Critical Control Point) was developed, which is an effective preventive measure for food safety. This research uses descriptive research with observational design conducted at UD.Teti Boga Catering Kupang City. The research subjects were 34 managers and workers at UD. Teti Boga Catering. The results showed the food quality control system at UD. Teti Boga Catering from the layout, receipt of raw materials, preparation and processing of raw materials to distribution that is not in accordance with standards. Thus the Company needs to schedule regular training on GMP and SSOP for employees, to make them aware and remind employees about the importance of sanitation hygiene in food safety.